A disseminação da informação mediada por novas tecnologias e a educação do usuário na biblioteca universitária - Dias, Simone Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
To ameliorate the quality of the services in the academicals libraries have been a constant preoccupation of the libraries professionals that work and conduct these services, or just, of the one that use them. The changes provoked mainly by computer's use make possible significant progress in what refers in the access to the library's computerized catalogs, to the data's bases on-line (bibliographical and textual) considering the information's speed and the inclusion of the search, that can contribute indirectly for the personal development as well as the society like a whole. It's necessary to disseminate and to usufruct the information with quality; for this, it's necessary to dominate all of the resources products and services available for the UNESP's Library in Marília-SP, focus of this research with the objective of been particularized the user's profile, prepare him to seek and find the information's that he needs and that the Library filters addressing them for your public. Thus, the option for the interview's technique applied to get information's whose the result show the professional's necessity to have the domain and specific abilities to exercise with competence the dissemination of the information, as well as for education (prepare the user in the handling of search techniques, through nets of computers and too much electronic technologies, in a continuo process that evolves the interaction between the user and the information's professional, in the dissemination of the information.

Melhorar a qualidade dos serviços nas bibliotecas universitárias tem sido uma preocupação constante dos profissionais bibliotecários que trabalham e administram esses serviços; ou, simplesmente, dos que se utilizam deles. As mudanças provocadas principalmente pelo uso de computadores possibilitam avanços significativos no que se refere ao acesso aos catálogos informatizados da Biblioteca, às bases de dados on-line (bibliográficas e textuais), considerando-se a velocidade da informação e a abrangência da busca, que podem contribuir indiretamente para o desenvolvimento pessoal bem como da sociedade como um todo. É preciso disseminar e usufruir a informação com qualidade; para isso, é necessário dominar todos os recursos, produtos e serviços disponibilizados pela Biblioteca do Campus da UNESP, em Marília - SP, foco desta pesquisa com o objetivo de particularizar-se o perfil do usuário, prepará-lo para buscar e encontrar as informações que necessita e que a Biblioteca filtra, direcionando-as para o seu público. Assim, a aplicação da técnica de entrevista permitiu colher dados e informações cujo resultado mostrou as necessidades dos profissionais de ter domínio e habilidades específicas, a fim de exercer com competência a disseminação da informação, bem como para educar/preparar o usuário no manuseio de técnicas de busca, por meio de redes de computadores e demais tecnologias eletrônicas, num processo contínuo que envolve a interação entre o usuário e o profissional da informação, na disseminação da informação.
Keywords: Disseminação seletiva da informação; Tecnologia da informação; Educação de usuários - Bibliotecas universitárias; Estudo de usuários - Bibliotecas universitárias; Dissemination of the information; New technologies; Academical library; Professional librarians; User's education